Neurophysiological Evidence of Compensatory Brain Mechanisms Underlying Attentional-Related Processes in Symptomatically Remitted Patients with Schizophrenia - Chen, Guoliang; Ding, Weiyan; Zhang, Lei; Cui, Hong; Jiang, Zhongdong; Li, Yansong (Frontiers in Psychology, 2017)
A recent electrophysiological study suggests existing compensatory brain activity as a mechanism for functional recovery of visual attention detection (the capacity for detecting external cues) in symptomatically remitted schizophrenia patients. Despite such evidence, little is known about other aspects of attentional-related processes in schizophrenia during clinical remission, such as their capacity to concentrate on the task at hands without being interfered by distracting information. To this end, we recorded event-related brain potentials (ERPs) from 20 symptomatically remitted schizophrenia patients and 20 healthy controls while they engaged in a classic Stroop task. Symptomatically remitted patients showed comparable Stroop interference to healthy controls, indicating a degree of functional recovery of such a capacity in these patients. On the neural level, the N450 over the fronto-central and central regions, a component of the ERPs related to conflict detection, was found across both groups, although patients presented a reduced N450 relative to healthy controls. By contrast, the amplitude of the sustained potential (SP) (600–800 ms) over the parieto-central and parietal regions, a component of the ERPs related to conflict resolution, was significantly increased in patients relative to healthy controls. Furthermore, such increased SP amplitude correlated positively with improved behavioral accuracy in symptomatically remitted patients with schizophrenia. These findings reveal that symptomatically remitted patients with schizophrenia increasingly recruited the parietal activity involving successful conflict resolution to offset reduced conflict detection. Therefore, this provides further insight into compensatory mechanisms potentially involving a degree of functional recovery of attentional-related processes in schizophrenia during clinical remission.